Konsep Dasar dan Teknik Manajemen Risiko Perbankan Syariah - Ahdiyat Agus Susila (Fakultas Ekonomi dan Bisnis Islam, 2018)
Often risks arise because of more than one choice and the impact of each option is not yet known for certain, as uncertain future. There is always an opportunity cost that follows every option taken. Thus, risks may be defined as the consequences of uncertain options that have the potential to lead to unexpected outcomes or other adverse impacts to decision makers. This is the classic definition of risk. From this definition, risk contains several dimensions, namely opportunity costs, potential losses or other negative impacts, uncertainty, and obtaining results that do not match expectations. It is with these demands that risks are measured, mitigated and monitored during the business process.